2022
DOI: 10.1093/cz/zoac082
|View full text |Cite
|
Sign up to set email alerts
|

Differences in predator-avoidance behavior between two invasive gobies and their native competitors

Abstract: Globally, fish are frequently introduced beyond their native range. Some, like Ponto-Caspian gobies, are becoming invasive, achieving high colonization rates and constituting frequent prey for native predators. However, little is known about the effectiveness of antipredator behaviors of the invaders, which may shape their role in the invaded community and contribute to the invasion success. We compared antipredator behaviors of invasive gobies and native fish species after their detection by the predator, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…It has been shown that the monkey and racer goby, compared to their native analogues, i.e. gudgeon G. gobio and European bullhead C. gobio, do not exhibit more effective defence behaviour in the face of a direct threat from European perch (Augustyniak et al 2022). In other laboratory studies, the behavioural responses of the monkey goby and gudgeon to predation cues (prey skin extracts) were less pronounced in invasive than native species (Kłosiński et al 2022).…”
Section: Ponto-caspian Gobies As Preymentioning
confidence: 95%
See 1 more Smart Citation
“…It has been shown that the monkey and racer goby, compared to their native analogues, i.e. gudgeon G. gobio and European bullhead C. gobio, do not exhibit more effective defence behaviour in the face of a direct threat from European perch (Augustyniak et al 2022). In other laboratory studies, the behavioural responses of the monkey goby and gudgeon to predation cues (prey skin extracts) were less pronounced in invasive than native species (Kłosiński et al 2022).…”
Section: Ponto-caspian Gobies As Preymentioning
confidence: 95%
“…Additionally, it shows that native predators can efficiently learn how to exploit gobies as new prey resources, despite there being no native counterparts of this family in European freshwaters where surveys were conducted. Laboratory studies (Augustyniak et al 2022;Kłosiński et al 2022) suggest that the gobies might be relatively easily accessible prey for some predators. It has been shown that the monkey and racer goby, compared to their native analogues, i.e.…”
Section: Ponto-caspian Gobies As Preymentioning
confidence: 99%
“…They represent a specific group of benthic, bladderless freshwater and brackish water fish, associated with shelters (Błońska et al., 2016; Charlebois et al., 1997; Kakareko, 2011) and exhibiting burst‐and‐hold swimming mode (Egger et al., 2021). Although they live at the bottom, they show dynamic escapes from predation (Augustyniak et al., 2023) and are capable of overcoming currents (Jermacz et al., 2015; Kakareko, 2011). Thus, in contrast to their generally low locomotor and metabolic demands, these fish rely on burst increases in activity.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of prey escape behaviour between different fishes are rare (Scharf et al., 2003; Webb, 1984a, 1986), with few examples that include benthic prey (Augustyniak et al., 2023). Many comparisons are focused on the effect of stickleback armouring due to predator presence (Marchinko, 2009; McLean & Godin, 1989; Paccard et al., 2018).…”
Section: Introductionmentioning
confidence: 99%